From Colonialism to International Aid External Actors and Social Protection in the Global South - Schmitt, Carina (Global Dynamics of Social Policy, 2020)
This open access volume addresses the role of external actors in social protection in the Global South, from the Second World War until today, analysing the influence of colonial powers, superpowers during the Cold War and contemporary donor agencies. Following an introduction to the analysis of external actors in social policy making in the Global South, the contributions explore which external actors were dominant in the decades after World War II, and how they shaped early and contemporary social protection making in developing countries. The latter half of the collection elucidates important players in the contemporary transnational social policy arena, such as donor organizations and international organizations, and critically evaluates the potential for and limits of the explanatory power of external actors in social protection making in the Global South, considering the relative contribution of external and domestic influences. By examining how transnational relationships and external actors have influenced the formation, development and transformation of social policies in the developing world, this collection will be an invaluable resource for scholars interested in social protection in the Global South from a range of disciplines. These include political science, social policy, and sociology, as well as historians of the welfare state, international relations scholars and scholars working on global and transnational social policy and development policy.